2017
DOI: 10.1016/j.jaac.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Inferior and Orbital Frontal Thickness in Adolescent Bulimia Nervosa Persists Over Two-Year Follow-Up

Abstract: Objective Cross-sectional data suggest functional and anatomical disturbances in inferior and orbital frontal regions in bulimia nervosa (BN). Using longitudinal data, we investigated whether reduced cortical thickness (CT) in these regions arises early and persists over adolescence in BN, independent of symptom remission, and whether CT reductions are markers of BN symptoms. Method Thirty-three adolescent females with BN symptoms (BN or other specified feeding or eating disorder) and 28 healthy adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 47 publications
2
30
1
Order By: Relevance
“…Reduced cortical thickness was also reported in fully and partially remitted BN patients by Cyr et al (2017), specifically in the right inferior frontal gyrus compared to healthy adolescents, possibly accounting for deficits in cognitive functions of learning, control, and reward. Moreover, remitted BN patients were found to exhibit neurobiological alterations in terms of neuroendocrine imbalances (diurnal hyposecretion of cortisol) thought to play an important role in signaling satiety and hunger (Birketvedt et al, 2006).…”
Section: Neurophysiological Functioningmentioning
confidence: 81%
“…Reduced cortical thickness was also reported in fully and partially remitted BN patients by Cyr et al (2017), specifically in the right inferior frontal gyrus compared to healthy adolescents, possibly accounting for deficits in cognitive functions of learning, control, and reward. Moreover, remitted BN patients were found to exhibit neurobiological alterations in terms of neuroendocrine imbalances (diurnal hyposecretion of cortisol) thought to play an important role in signaling satiety and hunger (Birketvedt et al, 2006).…”
Section: Neurophysiological Functioningmentioning
confidence: 81%
“…Findings from studies of healthy (Casey et al, ; Diamond, ) and ill (Emond, Joyal, & Poissant, ; Marsh, Zhu, Wang, Skudlarski, & Peterson, ; Raz et al, ) individuals indicate that fronto‐striatal circuits underlie the capacity for self‐regulatory control. Previous MRI findings suggest that fronto‐striatal circuits are structurally (Cyr et al, ; He, Stefan, Terranova, Steinglass, & Marsh, ; Marsh et al, ) and functionally (Cyr et al, ; Lock, Garrett, Beenhakker, & Reiss, ; Marsh et al, ; Skunde et al, ) abnormal in BN. These disturbances likely contribute to the LOC over eating behaviors that characterize the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Lower bilateral frontal pole volume at baseline did not persist over time, but volume was correlated negatively with objective binge-eating episode frequency. Similarly, the number of vomiting episodes was negatively associated with averaged cortical thickness over time in the lateral OFC and IFC orbitalis (Cyr et al, 2017). Conversely, a study on recovered BN patients compared with HC found no significant differences in GM volume.…”
Section: Volumetric Changesmentioning
confidence: 91%
“…Indeed, some studies indicate that alterations in volume are present in current patients, but not recovered patients, and that these positively correlate with symptom severity (Cyr et al, 2017;Wagner et al, 2006). Some of the studies investigating multiple aspects discussed in this review show considerable promise by using a consolidative approach.…”
Section: Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation